Development of Picture Storybook Media to Improve Students Reading Skills in Learning Pancasila Education in Class V State Elementry SD Negeri 02 Ngaliyan Semarang - Octaviany, Niken Ayu Nur; Prasetyaningtyas, Fitria Dwi (FKIP - Universitas Riau, 2025)
This study was motivated by the low interest and reading ability of fifth grade students of Sd Negeri 02 Ngaliyan Semarang, as well as the lack of use of interesting learning media in learning Pancasila Education. The purpose of this study was to develop, test the feasibility, and assess the effectiveness of picture storybook media in improving student learning outcomes. The research method used is Research and development (R&D) with the ADDIE development model which includes stages (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research subjects included teachers and fifth grade students of Sd Negeri 02 Ngaliyan Semarang. Data were collected through observation, interview, questionnaire, and pretest and posttest. The results showed that the picture storybook media was feasible to use based on the validation results of material, media, and language experts with very good categories. In addition, the results of the effectiveness test showed a significant increase in student learning outcomes after using the media. Thus, it can be concluded that the development of picture storybooks is effective in increasing students' interest and ability to read as well as learning outcomes in Pancasila Education subjects.